Coding and decoding libraries of sequence-defined functional copolymers synthesized via photoligation - Nicolas Zydziak (Nature Portfolio, 2016)
Controlling the molecular sequence of polymers and oligomers is a challenging task. Here the authors use a photoligation approach to synthesise macromolecules with functionality at defined positions throughout the chain, and additionally decode the sequence information via tandem mass spectrometry.